2021
DOI: 10.1038/s41598-021-03325-5
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mutant pigs by lipofection-mediated genome editing in embryos

Abstract: The specificity and efficiency of CRISPR/Cas9 gene-editing systems are determined by several factors, including the mode of delivery, when applied to mammalian embryos. Given the limited time window for delivery, faster and more reliable methods to introduce Cas9-gRNA ribonucleoprotein complexes (RNPs) into target embryos are needed. In pigs, somatic cell nuclear transfer using gene-modified somatic cells and the direct introduction of gene editors into the cytoplasm of zygotes/embryos by microinjection or ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…To the best of our knowledge, only one research group has reported the use of the lipofection method in porcine ZP-free oocytes and ZP-free embryos with some success [26][27][28][29]. As the ZP is a significant physical barrier and appears to reduce the effectiveness of lipofectamine, these researchers treated ZP-free oocytes and ZP-free embryos and achieved a moderate mutation rate (ranging from 8% to 57%) with a high level of mosaicism (ranging from 87.5% to 100% of mutant embryos) [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, only one research group has reported the use of the lipofection method in porcine ZP-free oocytes and ZP-free embryos with some success [26][27][28][29]. As the ZP is a significant physical barrier and appears to reduce the effectiveness of lipofectamine, these researchers treated ZP-free oocytes and ZP-free embryos and achieved a moderate mutation rate (ranging from 8% to 57%) with a high level of mosaicism (ranging from 87.5% to 100% of mutant embryos) [27].…”
Section: Discussionmentioning
confidence: 99%
“…As the ZP is a significant physical barrier and appears to reduce the effectiveness of lipofectamine, these researchers treated ZP-free oocytes and ZP-free embryos and achieved a moderate mutation rate (ranging from 8% to 57%) with a high level of mosaicism (ranging from 87.5% to 100% of mutant embryos) [27]. Later, with further optimization of the system using ZP-free embryos, they generated mutant embryos for different genes and produced genetically modified piglets with a monoallelic mutation for the MSTN gene [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1). The gRNAs targeting KDR and PDX1 were evaluated in our previous study ( Hirata et al., 2021 ; Tanihara et al., 2020 ). The oocytes incubated for each time point were mechanically freed from cumulus cells in Dulbecco's PBS (DPBS; Invitrogen Co.) supplemented with 1 mg/ml hyaluronidase (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%